2020
DOI: 10.1109/access.2020.2975379
|View full text |Cite
|
Sign up to set email alerts
|

Design of Notched-Wideband Bandpass Filters With Reconfigurable Bandwidth Based on Terminated Cross-Shaped Resonators

Abstract: In this paper, a series of novel reconfigurable-bandwidth notched-wideband bandpass filters (NWB BPFs) with controllable notch bands are proposed. The proposed filters start from a passive filtering structure, which is formed by a terminated cross-shaped resonator (TCSR) with a pair of parallel-coupled lines and two open-ended stubs. Theoretical analysis finds that the filter bandwidth can be independently controlled by the TCSR, while the center frequencies and bandwidth of notch bands are mainly controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…In summary, without a need for extra filtering circuits, the design presented in [71] offers a new solution for current and future filtering antenna designs. Additionally, many reconfigurable microstrip filter-antenna structures have been presented and discussed [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. In [79], a multiband tunable filter cascaded with a monopole antenna for cognitive radio communications is presented.…”
Section: Microstrip Filter-antenna (Filtenna) Integrationmentioning
confidence: 99%
“…In summary, without a need for extra filtering circuits, the design presented in [71] offers a new solution for current and future filtering antenna designs. Additionally, many reconfigurable microstrip filter-antenna structures have been presented and discussed [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. In [79], a multiband tunable filter cascaded with a monopole antenna for cognitive radio communications is presented.…”
Section: Microstrip Filter-antenna (Filtenna) Integrationmentioning
confidence: 99%
“…In all the reported research works, the filters are designed to offer tuning over a narrow range of frequencies. In most of the said works, bandwidth reconfiguration is obtained by varying the lower/upper transmission zeros while retaining the centre frequency (Bi et al , 2020; Bi et al , 2021; Arain et al , 2020). The research reported by Chen et al (2021) has realized bandwidth reconfiguration by varying the centre frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, wideband filters with notched bands are still in great need. Many methods have been reported to realize one or more notched frequencies in the passband, such as resonators 1 , exponential tapered impedance line 2 , embedded open stubs 3 5 , varactor-loaded shorted-slots 6 , asymmetric structure 7 , terminated capacitance 8 , signal interaction between main and minor paths 9 , 10 , folded coupling line 11 , 12 , and multi-mode resonator (MMR) 13 18 . Most of them use transmission poles and zeros to achieve good wideband performance and controllable notched bands, which can effectively suppress interference 19 – 26 .…”
Section: Introductionmentioning
confidence: 99%